Prospective Assessment of the Performance of a Combi-Rapid Diagnostic Test to Accurately Diagnose Malaria and Detect C-Reactive Protein in Selected Settings in India - Bina Srivastava; Anup Anvikar; Deepali Anvikar; Supriya Sharma; Naseem Ahmed; Deendayal Swarnkar; Manoj K. Das; Khageshwar Pradhan; Kuldeep Singh; Alex Eapen; Sanal Kumar; Thomas Keller; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Management of malaria-negative febrile patients is hampered by a lack of rapid diagnostic tests (RDTs) that guide treatment decisions, increasing the risks of antibiotic overuse and antimicrobial resistance. The simultaneous detection of malaria and C-reactive protein (CRP), a potentially useful host biomarker for distinguishing between bacterial and nonbacterial infections, using RDTs could help address this challenge. A prospective study was conducted at seven sites in India from April to December 2019 to evaluate the performance of the SD BIOSENSOR STANDARD™ Q Malaria/CRP Duo Test (SD BIOSENSOR, Gyeonggi-do, South Korea) against expert microscopy for malaria and against a commercial biochemistry kit for CRP, with a total of 1,799 patients with suspected malaria included in the analysis. The prevalence of malaria parasitemia according to microscopy was 13.3% (3.3% Plasmodium falciparum [ P. falciparum ], 10.1% Plasmodium vivax [ P. vivax ]). The Duo test was used to diagnose malaria, P. falciparum , and P. vivax infections, with sensitivities of 97.9% (95% CI: 95.2%–99.1%), 91.4% (95% CI: 81.4%–96.3%), and 95.0% (95% CI: 90.7%–97.3%), respectively. The Duo test performed better for detecting pan malaria and P. vivax infections compared with the routine RDT (SD BIOLINE Malaria P.f/pan antigen test; sensitivity 86.1% [95% CI: 81.1%–89.9%] and 79.9% [95% CI: 73.4%–85.1%] for malaria and P. vivax , respectively). The Duo test’s sensitivity and specificity for detecting CRP at levels of 20 mg/L or higher were estimated at 87.4% (95% CI: 84.7%–89.7%) and 94.0% (95% CI: 92.4%–95.3%), respectively. The satisfactory agreement between test results and standard reference methods suggests that the test can be used in malaria-endemic settings; however, additional studies are needed to assess its impact on malaria testing and antibiotic prescription practices.